Mapping Soil Temperature in Zaamin National Nature Park Using Meteorological Data Using ArcMap Software - Khobiljon Saqiyev (Indonesian Journal Publisher, 2025)
The article explores the mapping of soil temperature in the Zaamin National Nature Park using ArcMap software based on meteorological data. The results of the study show that global climate change has a serious impact on the local conditions, including the soil of the Zaamin National Nature Park. As a result of 42 years of observations carried out between 1981 and 2022, it was found that the soil temperature of the Zaamin National Nature Park increased by an average of 1.5-2.5○C. The results obtained are of great practical importance for mapping the temperature of soils in protected natural areas; they make it possible to carry out reclamation work in the territories, cleanup of dried plant waste and other practical work